Genomic Selection Project meeting the variety needs of future farmers - Mamo, Teshale Assefa; Nchanji, Eileen; Birachi, Eliud (2023)
Crop varietal and breeding lines selection is predominantly performed in controlled research stations, which may not properly represent African farmers’ crop growing environmental conditions. To address this, the project seeks to test the bean breeding lines in real farmers’ bean farming environments by implementing genomics-assisted on-farm testing using the tricot approach across a wide range of bean-growing environments. This approach addresses the performance of breeding lines/varieties between on-farm and on-station testing, particularly the challenges faced by women farmers, who typically experience low-input management conditions. By incorporating gender-intentional participatory methods and considering diverse perspectives, the project aims to accelerate genetic gains and develop varieties tailored to local environmental conditions and empower farmers in the decision-making processes of varietal development that can address the need of farmers and consumers.